2004
DOI: 10.1007/s00425-004-1269-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and benzyl adenine on development and function of microhairs of Zea mays L

Abstract: Bicellular microhairs are present on the surfaces of leaves of grasses with the exception of the Pooideae. In some halophytic grasses, these glandular hairs secrete salt, suggesting the intriguing question 'can the microhairs of grasses that do not normally encounter salinity also secrete salt?' Microhairs were counted in replicas of the adaxial and abaxial surfaces of leaves of various ages of maize plants growing either in the absence of salt or in the presence of 40, 80 or 120 mM NaCl. The number of microha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…2). These results are consistent with those for prickles of maize (Zea mays L.) with BA treatment and macrohairs of Rhodes grass (Chloris gayana Kunth) with MeJA treatment (Kobayashi et al 2010;Ramadan and Flowers 2004). An increase in trichome density in response to BA or jasmonates has been reported previously in dicotyledonous plants such as Arabidopsis, Artemisia annua and Lycopersicon esculentum (Boughton et al 2005;Maes et al 2008Maes et al , 2011Traw and Bergelson 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2). These results are consistent with those for prickles of maize (Zea mays L.) with BA treatment and macrohairs of Rhodes grass (Chloris gayana Kunth) with MeJA treatment (Kobayashi et al 2010;Ramadan and Flowers 2004). An increase in trichome density in response to BA or jasmonates has been reported previously in dicotyledonous plants such as Arabidopsis, Artemisia annua and Lycopersicon esculentum (Boughton et al 2005;Maes et al 2008Maes et al , 2011Traw and Bergelson 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In Arabidopsis, jasmonic acid (JA), a jasmonate, increases the size and density of trichomes, and 6-benzylaminopurine, a cytokinin, reduces trichome size but increases their density (Maes et al 2008). Since application of these two hormones increases trichome density in Poaceae plants (Kobayashi et al 2010;Ramadan and Flowers 2004), their application was also expected to affect trichome size for plants in the Poaceae, including wheat.…”
Section: Introductionmentioning
confidence: 98%
“…Rozema et al (1977) found increases in the number of salt glands in Glaux maritime as external salt concentrations increased, while Liphschitz et al (1974) found the number of glands in Chloris gayana unchanged by 5-day exposure to salt. However, sprays of the synthetic cytokinin benzyl adenine (BA) can increase the number of glands in Chloris guayana and in maize, BA treatment increased the loss of sodium (Ramadan and Flowers 2004). In maize, this increased Na ?…”
Section: Introductionmentioning
confidence: 99%
“…glands that originally performed some other function is unclear, but it is difficult, at least in the Poaceae, to get glandular hairs on non-halophytes (such as Zea mays L.) to secrete salt (Ramadan and Flowers 2004).…”
Section: Cressa Cretica)mentioning
confidence: 99%